Optimization of hydrocolloid levels in medium-chain triglyceride-enriched soymilk by response surface methodology - Villones, Irene Tonette Y.; Dumilod, Benelyn D. (Quezon City College of Home Economics, University of the Philippines Diliman, 2019)
Abstract
Thesis (B.S. Food Technology)--University of the Philippines Diliman
Keywords: Soymilk